Exploring individual quality in a wild population of red deer. - Moyes, K; Morgan, B; Morris, A; Morris, S; Clutton-Brock, T; Coulson, T (2009)
1. A wide range of measures are used to quantify 'individual quality', with the term often used but not defined. 2. Here we use detailed data from a population of red deer (Cervus elaphus) to assess whether frequently used measures of individual quality are well correlated, and therefore likely to lead to comparable ecological and evolutionary insight in analyses. 3. Correlations between measures were usually small, indicating that individuals may be considered high quality for one trait, but low quality for another. 4. By using principal component analysis, we illustrate that there are potentially many varied individual life-history tactics within a population. 5. This variation in tactics makes it challenging to characterize individual quality as a simple scalar; measures of heterogeneity in ecological studies should therefore be both species and question specific.